Strategi Bisnis Coffee Shop “Nordic” Pada Kondisi Pasar Uncertainly Di Surabaya - Sebastian Tirta Danu; Kuswandi; Bambang Subiantoro (AMMA : Jurnal Pengabdian Masyarakat, 2024)
This article examines Nordic Coffee's coffee shop strategy to survive the uncertain market conditions. Fluctuating market conditions, such as changing consumer trends and economic uncertainty, are the biggest challenges facing the coffee industry today. The methodology used includes market analysis, direct observation in the field, and interviews with management and customers. This research examines the strategies of product diversification, service quality improvement, technology utilization for operational efficiency, and digital marketing campaigns. The results show that Nordic Coffee successfully increased customer appeal by expanding its product range, improving customer interaction, and using digital platforms to increase brand awareness. The implications of this study highlight the importance of adaptability and innovation in business strategy to cope with uncertain market dynamics. In summary, this article provides insights into successful strategies that coffee shops like Nordic Coffee can implement to maintain business continuity despite changing external challenges.